2000
DOI: 10.2337/diacare.23.9.1359
|View full text |Cite
|
Sign up to set email alerts
|

Familial clustering of arterial blood pressure, HDL cholesterol, and pro-insulin but not of insulin resistance and microalbuminuria in siblings of patients with type 2 diabetes.

Abstract: OBJECTIVE -To test the hypothesis that selected abnormalities cluster in type 2 diabetic families. Offspring of patients with type 2 diabetes have a 40-60% chance of developing type 2 diabetes and an increased frequency of impaired glucose tolerance (IGT) or unknown diabetes. These offspring also show metabolic abnormalities of type 2 diabetes, such as insulin resistance, high insulin and pro-insulin, low HDL cholesterol levels, arterial hypertension, and microalbuminuria.RESEARCH DESIGN AND METHODS -We studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
(56 reference statements)
1
16
0
1
Order By: Relevance
“…[4][5][6][7][8][9] Similar findings have also been found in the offspring of individuals with type 2 DM, this mainly attributed to the increased risk of obesity, hyperinsulinemia and glucose intolerance. 7,[10][11][12] However, it is not yet clear whether a family history of DM per se is associated with dyslipidemia, or dyslipidemia is related to the obesity, hyperinsulinemia or glucose intolerance, usually present in subjects with family history of type 2 DM.…”
Section: Introductionsupporting
confidence: 68%
“…[4][5][6][7][8][9] Similar findings have also been found in the offspring of individuals with type 2 DM, this mainly attributed to the increased risk of obesity, hyperinsulinemia and glucose intolerance. 7,[10][11][12] However, it is not yet clear whether a family history of DM per se is associated with dyslipidemia, or dyslipidemia is related to the obesity, hyperinsulinemia or glucose intolerance, usually present in subjects with family history of type 2 DM.…”
Section: Introductionsupporting
confidence: 68%
“…Further, male and female first degree relatives of PCOS probands have been reported with elevated insulin levels (34). The significant correlations between PCOS probands and their sisters for glucose levels is consistent with a heritable component to this trait (35). One of the possible interpretations of the significant bimodal distribution of insulin levels among the sisters is that this may be a monogenic trait controlled by two alleles at an autosomal locus (13,30).…”
Section: Discussionmentioning
confidence: 51%
“…Previous evidence has shown that the offspring of individuals with type 2 diabetes have an increased risk of developing type 2 diabetes, with defects in early beta cell secretion [22][23][24][25]. It has also been suggested that these offspring have early autonomic dysfunction, even in the absence of glucose intolerance [26], and more often display metabolic abnormalities with high insulin levels and arterial hypertension [27,28]. In a previous community-based cohort, parental diabetes appeared to be an independent predictor of longitudinal changes in both systolic and diastolic BPs in the offspring, regardless of race and sex [29].…”
Section: Discussionmentioning
confidence: 99%